2009
DOI: 10.1016/j.cell.2009.05.046
|View full text |Cite
|
Sign up to set email alerts
|

CD47 Is Upregulated on Circulating Hematopoietic Stem Cells and Leukemia Cells to Avoid Phagocytosis

Abstract: Summary Macrophages clear pathogens and damaged or aged cells from the blood stream via phagocytosis. Cell-surface CD47 interacts with its receptor on macrophages, SIRPα, to inhibit phagocytosis of normal, healthy cells. We find that mobilizing cytokines and inflammatory stimuli cause CD47 to be transiently up-regulated on mouse hematopoietic stem cells (HSCs) and progenitors just prior to and during their migratory phase, and that the level of CD47 on these cells determines the probability that they are engul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
1,192
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,355 publications
(1,231 citation statements)
references
References 40 publications
34
1,192
3
2
Order By: Relevance
“…However, when bone marrow HSCs were mobilized out of bone marrow, they upregulated CD47. 11 Ide et al 30 demonstrated that the overexpression of CD47 on donor cells or treatment of recipient mice with soluble CD47 enhanced the engraftment of xenogenic donor cells. This suggests that the overexpression of CD47 may be correlated with higher resistance to phagocytosis by macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when bone marrow HSCs were mobilized out of bone marrow, they upregulated CD47. 11 Ide et al 30 demonstrated that the overexpression of CD47 on donor cells or treatment of recipient mice with soluble CD47 enhanced the engraftment of xenogenic donor cells. This suggests that the overexpression of CD47 may be correlated with higher resistance to phagocytosis by macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-CD47 monoclonal antibodies inhibiting the interaction of CD47 and SIRPa promote the phagocytosis of tumor cells by macrophages, and also by monocytes and neutrophils. [9][10][11] Cancer cells including acute myelogenous leukemias, 11,12 lymphomas, 13,14 and various solid cancers [15][16][17] express CD47 at a high level, and can be phagocytosed by macrophages in the presence of blocking antibodies to CD47. [11][12][13][14][15][16][17] In those cases where the tumor-initiating cells (or cancer stem cells) are known, for example, from acute myelogenous leukemias and bladder cancers, the tumor-initiating cells also upregulate CD47 expression, possibly to avoid phagocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…We realized that our AML LSC gene encoded a protein that is a "don't eat me" signal (226). We rapidly showed that CD47-negative HSCs cannot engraft in wild-type irradiated hosts (224). We found that normal HSCs mobilized by Cytoxan and G-CSF upregulated CD47 transiently, then extravasated into the bloodstream (224), whereupon they homed rapidly to the vascular sinusoids of bone marrow, spleen, and liver (224), presumably using integrin α 4 β 1 to bind luminal VCAM1, then followed their cell surface chemokine receptor CXCR4 and transmigrated across fields of perivascular sinusoidal macrophages to reach CXCL12-secreting niches (227)(228)(229)(230)(231).…”
Section: Cancer Stem Cells and The Therapeutics That Come From Themmentioning
confidence: 98%
“…We found that normal HSCs mobilized by Cytoxan and G-CSF upregulated CD47 transiently, then extravasated into the bloodstream (224), whereupon they homed rapidly to the vascular sinusoids of bone marrow, spleen, and liver (224), presumably using integrin α 4 β 1 to bind luminal VCAM1, then followed their cell surface chemokine receptor CXCR4 and transmigrated across fields of perivascular sinusoidal macrophages to reach CXCL12-secreting niches (227)(228)(229)(230)(231). Knockdown of leukemia cell CD47 led to their elimination by macrophages in vitro, and upon intravenous injection in vivo, they were removed by sinusoidal tissue macrophages (224). CD47-negative cell lines placed in vitro with macrophages usually are phagocytosed, whereas the same cells transfected with and expressing CD47 were not (224).…”
Section: Cancer Stem Cells and The Therapeutics That Come From Themmentioning
confidence: 99%
“…Tumor cells were shown to constitutively up-regulate CD47 expression in multiple tumor entities and animal models. Furthermore, over-expression of CD47 was a poor prognostic factor and correlated with increased pathogenicity [106][107][108][109][110]. Treatment of solid or hematopoietic tumors with either CD47-specific blocking antibodies or SIRPα-fusion proteins resulted in an increase in macrophage-dependent phagocytosis of tumor cells and a corresponding decrease in tumor size and number of metastases [107][108][109][110][111].…”
Section: Therapeutic Reprogramming Of Tumor-associated Macrophagesmentioning
confidence: 99%